Thermochronological insights into reactivation of a continental shear zone in response to Equatorial Atlantic rifting (northern Ghana). Issue 1 (December 2018) - Fernie, Nicholas; Glorie, Stijn; Jessell, Mark; Collins, Alan
Abstract West Africa was subjected to deformation and exhumation in response to Gondwana break-up. The timing and extent of these events are recorded in the thermal history of the margin. This study reports new apatite fission track (AFT) data from Palaeoproterozoic basement along the primary NE-SW structural trend of the Bole-Nangodi shear zone in northwestern Ghana. The results display bimodality in AFT age (populations of ~210-180 Ma and ~115-105 Ma) and length distributions (populations of 12.2 ± 1.6 and 13.1 ± 1.4 µm), supported by differences in apatite chemistry (U concentrations). The bimodal AFT results and associated QTQt thermal history models provide evidence for multiple cooling phases. Late Triassic – Early Jurassic cooling is interpreted to be related with thermal relaxation after the emplacement of the Central Atlantic Magmatic Province (CAMP). Early to middle Cretaceous cooling is thought to be associated with exhumation during the Cretaceous onset of rifting between West Africa and Brazil. Late Cretaceous – Cenozoic cooling can be related with exhumation of the Ivory Coast – Ghana margin and NNW-SSE shortening through western Africa. Furthermore, our data record differential exhumation of the crust with respect to the Bole-Nangodi shear zone, preserving older (CAMP) cooling ages to the south and younger (rifting) cooling ages to the north of the shear zone, respectively. This suggests that the Palaeoproterozoic BN shear zone was reactivated during the Cretaceous as a result of deformation in the Equatorial Atlantic region of Africa.